Work-Related Upper Limb Symptoms in Hand-Intensive Health Care Occupations: A Cross-Sectional Study With a Health and Safety Perspective. Issue 1 (17th October 2018) - Greiner, Birgit A; Nolan, Sheilah; Hogan, Dervla A M
Abstract: Background: Research with physical therapists reveals high rates of work-related musculoskeletal injuries, especially low back pain, with early career onset. Less focus has been given to upper limb disorders (ULDs) in these professionals, who frequently perform repetitive arm/hand and precision finger motions during work. Objective: The objective was to estimate prevalence of body-site–specific upper limb (UL) symptoms and diagnosed ULDs in Irish chartered physical therapists, physiotherapists, and athletic therapists, with adjustment for leisure time injury, and document first onset of specific UL symptoms. Design: The design was a cross-sectional survey (N = 347) using random sampling (physiotherapists in private practice), proportionate cluster sampling (hospital-based physiotherapists), and all-population sampling (physical therapists and athletic therapists). Methods: The methods used were a postal questionnaire with annual, current, and incapacitating UL symptoms (neck, shoulders, elbows, wrists, fingers, thumbs) (Nordic Questionnaire); symptom onset; diagnosed UL disorders; and sociodemographics; prevalence with 95% CIs, and adjusted prevalence (general linear modeling). Results: Adjusted annual prevalence of UL symptoms in at least 1 body site was 78.1% (95% CI = 71.4–82.2), and of incapacitating symptoms was 21.0% (95% CI = 16.4–27.0). Shoulder (53.2%, 95% CI = 47.9–58.7), neck (49.4%, 95% CI = 44.2–55.0), and thumbs (46.1%, 95% CI = 40.7–51.5) were mostly affected. Hospital-based therapists had a significantly higher prevalence of incapacitating symptoms compared with others (35.7% vs 23.3%). Respondents totaling 28.2% had at least 1 lifetime diagnosis of ULD, most commonly shoulder tendonitis (12.5%, 95% CI = 8.4–15.3) and overuse syndrome (11.8%, 95% CI = 8.4–15.3). First onset was mostly after 5 years working as a therapist; however, this differed by anatomical site. Limitations: A cross-sectional study design limited interpretation of symptoms as work-related causes. Conclusions: The high prevalence of ULD and symptoms warrants attention from occupational health and safety personnel. Training in injury prevention and risk assessment should be provided during education and as part of continuing education.